Squamoid eccrine ductal carcinoma: an extremely rare variant of sweat duct carcinoma - (:unkn) unknown (MEDCOM LTD, 2020)
Squamoid eccrine ductal carcinoma (SEDC) is an extremely rare variant of sweat duct carcinoma. Herein, we report a case of an 80-year-old female who presented with an ulcerated plaque on her forehead. An initial punch biopsy revealed an invasive tumour with squamous features. Subsequently, excisional biopsy revealed squamous and ductal areas, with frequent mitosis and extensive perineural invasion. The patient has been disease-free for four years. SEDCs have a better prognosis than other sweat duct carcinomas. Differential diagnoses for SEDCs include squamous cell carcinoma, microcystic adnexal carcinoma, porocarcinoma and metastatic tumours. There is a high possibility of misdiagnosing SEDC as squamous cell carcinoma, particularly in small punch and shave biopsies.
Keywords: Microcystic adnexal carcinoma; squamoid eccrine ductal carcinoma; sweat duct carcinoma